Identificación y evaluación de los procesos operativos para lograr la optimización de la producción en la empresa la madrileña - Guilcamaigua Pastuña, José Vicente (2017)
The research done at La Madrileña is aimed at optimization of production, with this intention it is proposed: to diagnose the current situation of the production process in relation to raw material; determine the losses and their effect on production; to finally formulate a proposal of optimization of the production. Methodologically the study was based on the design and execution of factorial experiments, Pareto diagram, elaboration of flowcharts, and determination of shrinkage. The most demanded products were identified with the Pareto diagram, with the most vital being: special sausage with a production of 9.5%; smoked sausage with 6.5% and special button with 13%, which together represent 29% of the total production. In the monthly production for smoked sausage the raw material to be processed is 6,900 kilograms, the reduction of the process is 15% and the cost of production is of 2.30 dollars per kilogram; in the monthly production for special button the raw material to be processed is 14,240 kilograms, the reduction of the process is 18% and the production cost is 2.04 dollars per kilogram; in the monthly production for special sausage the raw material to be processed is 10,050 kilograms, the total loss of the process is 23% and the cost of production is of 2.58 dollars per kilogram....